The Societal Integration of International Law: Quantifying Normative Compliance and Global Governance Efficacy - Nuriddinova , Dilnura; Qodirova , Rayxona (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
The intersection of international jurisprudence and global societal architecture demands rigorous empirical evaluation to determine the efficacy of cross-border normative compliance. This investigation quantifies the assimilation rate of international legal frameworks into domestic societal structures, examining the functional mechanisms that drive sovereign adherence to global mandates. Utilizing a mixed-methods socio-legal paradigm, we evaluated 412 distinct treaty implementation cycles across 45 developing and developed jurisdictions between 2018 and 2025. The analysis targeted the enforcement trajectories of human rights protocols and transnational economic regulations against localized socio-political resistance metrics. Implementation of formalized international legal mandates yielded highly stratified societal compliance outcomes. Advanced economies demonstrated an 84.5% baseline adherence to integrated soft-law directives, whereas transitional demographic regions registered a 42.1% compliance rate (p < 0.001), heavily constrained by competing domestic socio-cultural variables. The integration of targeted economic sanctions as an enforcement mechanism produced an unintended 31.4% increase in societal alienation within the penalized regions, effectively undermining long-term institutional legitimacy. The empirical data reveals that standard monolithic approaches to international law fail systematically unless structurally adapted to regional sociological realities. Restructuring global governance frameworks to prioritize localized socio-legal assimilation over rigid, punitive enforcement represents a non-negotiable strategic necessity to optimize transnational legal efficacy and secure unified global societal stability.